Enhancing anti-tumor effect of ultrasensitive bimetallic RuCu nanoparticles as radiosensitizers with dual enzyme-like activities. (November 2022) - Hu, Bochuan; Xiao, Xiaohui; Chen, Pin; Qian, Jieying; Yuan, Guotao; Ye, Yayi; Zeng, Lingli; Zhong, Suqin; Wang, Xiaoli; Qin, Xiaohua; Yang, Yuedong; Pan, Yue; et al.
Abstract: Radiotherapy (RT), through the generation of reactive oxygen species (ROS) and DNA damage to tumor cells caused by high-energy irradiation, has been a widely applied cancer treatment strategy in clinic. However, the therapeutic effect of traditional RT is restricted by the insufficient radiation energy deposition and the side effects on normal tissues. Recently, multifunctional nano-formulations and synergistic therapy has been developed as attractive strategies for used to enhancing the efficacy and safety of RT. Herein, we show that a bimetallic nanozyme (copper-modified ruthenium nanoparticles, RuCu NPs), containing the high atomic number (Z) element Ru as a novel radiosensitizer, offers an ideal solution to RT sensitization, with ultrasensitive peroxidase (POD)-like activity and catalase (CAT)-like activity. Density functional theory (DFT) calculations also clarified the optimal POD-like catalytic ratio of RuCu NPs and further revealed the mechanism of its supper catalytic activity. Under X-ray exposure, RuCu NPs coated with poly(ethylene glycol) (PEG) exhibited simultaneously improved the ROS production and relieved tumor hypoxia in the acid tumor microenvironment (TME), and demonstrated remarkable therapeutic efficacy in the MDA-MB-231 breast cancer model. Our results provide a proof-of-concept for a RT sensitization strategy, which combine the intrinsic nature of high-Z element and the advantages of nanozymes to overcome the tricky drawbacks existed in radiotherapy, and further open a new direction of exploring novel nanozyme-based strategies for tumor catalytic therapy and synergistic radiotherapy.